GC–MS based tentative identification of γ-sitosterol from Brassica nigra seeds and evaluation of its anticancer potential: An integrated in vitro and in silico study - Sajidur Rahman Akash; Tawsif Al Arian; Sumaya Alam Mim; Md. Raihan Chowdhory; Moushumi Afrin Eva; Dipalok Karmaker; Afrin Akter; Md Asadujjaman; Lamia Nur; Bijoy Kumer Ghosh; Chayan Talukder; Md. Torequl Islam; et al. (PLoS ONE, 2026)
Cervical cancer remains a significant global health burden, particularly in developing countries where limited access to effective therapies contributes to high morbidity and mortality. Natural products derived from medicinal plants have emerged as promising sources of novel anticancer agents; however, identifying active compounds and elucidating their molecular mechanisms remain challenging. This study investigates the anticancer potential of Brassica nigra seed extract, with particular emphasis on γ-sitosterol as a bioactive compound relevant to cervical cancer therapy. Isopropanol extracts of B. nigra seeds were analyzed using GC–MS for phytochemical profiling. Cytotoxicity was assessed via MTT assay on HeLa (cervical cancer) and Vero (normal) cell lines, followed by a brine shrimp lethality bioassay. Anti-inflammatory activity was evaluated using protein denaturation and membrane stabilization assays, and thrombolytic activity was examined through a clot lysis assay. An integrated in silico approach was employed to evaluate γ-sitosterol, including oral drug-likeness prediction, target screening, protein–protein interaction network analysis, BRCA expression profiling, molecular docking, and 100 ns molecular dynamics simulations to explore its interaction with neuropilins and other cancer-related targets. The extract demonstrated dose-dependent cytotoxicity against HeLa cells (CC₅₀ = 0.36 mg/mL), while showing lower toxicity in Vero cells (CC₅₀ = 1.26 mg/mL), yielding a Selectivity Index of approximately 3.5, indicative of selective anticancer activity. Significant inhibition of protein denaturation (IC₅₀ = 74.8 µg/mL) suggested notable anti-inflammatory potential. GC–MS identified γ-sitosterol as a major constituent (17.33% peak area). Computational analyses revealed stable binding interactions of γ-sitosterol with key targets including TP53, AKT, and BRCA1, supporting its potential role as a multi-target modulator of apoptosis, survival signaling, and genomic stability pathways. Overall, B. nigra seed extract, enriched with γ-sitosterol, exhibits promising cytotoxic and anti-inflammatory activities. Further isolation, mechanistic validation, and in vivo studies are warranted to confirm its therapeutic potential in cervical cancer management.